Dirty Joe, the pirate : a true story - Harley, Bill, 1954- (HarperCollinsPublishers, 2008)
Dirty Joe and his pirate crew terrorize the seven seas in their quest for dirty socks, but they meet their match in Stinky Annie, whose favorite loot is pilfered underwear.